2019
DOI: 10.1016/j.istruc.2019.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Load capacity predictions of continuous concrete deep beams reinforced with GFRP bars

Abstract: Nine continuous concrete deep beams reinforced with glass fibre reinforced polymer (GFRP) bars were experimentally tested to failure. Three main parameters were investigated, namely, shear span-to-overall depth ratio, web reinforcement and size effect. The experimental results confirmed the impacts of web reinforcement and size effect that were not considered by the strut-and-tie method (STM) of the only code provision, the Canadian S806-12, that addressed such elements. The experimental results were employed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…As per the results, the load capacity of the beams was dramatically reduced as the a/h ratio increased due to a drop in the strut's angle of inclination. Zinkaah and Ashour [46] predicted the load capacity of continuous concrete deep beams strengthened with GFRP rebars. They showed that the expected loads of the specimens strengthened with GFRP rebars were overestimated by the upper bound analysis.…”
Section: Introductionmentioning
confidence: 99%
“…As per the results, the load capacity of the beams was dramatically reduced as the a/h ratio increased due to a drop in the strut's angle of inclination. Zinkaah and Ashour [46] predicted the load capacity of continuous concrete deep beams strengthened with GFRP rebars. They showed that the expected loads of the specimens strengthened with GFRP rebars were overestimated by the upper bound analysis.…”
Section: Introductionmentioning
confidence: 99%
“…From the literature, 106 beams with a shear span to depth ratio (a/d) of less than 2.5 were compiled (Abed et al, 2012; Abu-Obaida et al, 2018; Alam and Hussein, 2017; Andermatt and Lubell, 2013b; El-Sayed et al, 2012; Farghaly and Benmokrane, 2013; Guadagnini et al, 2006; Kim and Jang, 2014; Kim et al, 2014; Mahmoud and El-Salakawy, 2016; Nehdi et al, 2008; Razaqpur et al, 2004; Tottori and Wakui, 1993; Zinkaah and Ashour, 2019). The beams were only reinforced in the longitudinal direction without transverse reinforcement.…”
Section: Description Of Databasementioning
confidence: 99%
“…The authors also highlighted the need for further studies to refine the strut effectiveness factor, taking into account the non-linear effects of stress distribution. Zinkaah and Ashour (Zinkaah and Ashour, 2019) proposed another modification to the CSA STM effectiveness factor (CSA, 2012). The modification was assessed using nine continuous DBs reinforced with GFRP.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that failure was triggered by a major diagonal crack in the middle shear span between the load and interior support, and that the comparison between test results and code provisions, specifically the ACI Building Code (318-89) and CIRIA Guide 2, showed slight agreement. Zinkaah et al [7] and Zinkaah and Ashour [8] tested one steel-reinforced and nine (Glass Fiber Reinforced Polymer) GFRP-reinforced continuous shear-critical members. The experimental member load-carrying capacities were compared with capacities predicted by a strut-and-tie model (STM) following the American (ACI 318-2014) and Canadian (S806-2012) code guidelines.…”
Section: Introductionmentioning
confidence: 99%